Défis de l’intégration communautaire dans la conservation de la biodiversité en Afrique de l’Ouest : cas du site Ramsar du complexe lagunaire de Keta Lagoon, Ghana - El hadj Bara Dème; Grégoire Touron-Gardic; Kieran Deane; Anthony Adeea Mba; Senyo Adza; Lawrence Tetteh-Ocloo; Richard Gyimah; Precious Agbeko D. Mattah; Pierre Failler; Paul Silaï Tendeng (VertigO)
The aim of this article is to analyze the perceptions of local communities towards the Ramsar site of the Keta Lagoon complex, and on the evaluation of the main environmental issues weighing on this ecosystem. The research method combined semi-structured interviews with focus groups to gather in-depth qualitative data representative of local perceptions and dynamics, covering all six districts of the Keta Lagoon complex. The results show that the main threats identified by local communities around the Keta Lagoon complex are overexploitation of natural resources (mentioned by 70% of respondents), blocked canals, salinization and climatic disturbances. These threats aggravate the communities' dependence on their environment and have led to a significant deterioration in their living conditions over the last 10 - 20 years. Some 46% of those interviewed have little or no knowledge of the Ramsar site, while 42% have a good knowledge of the site. This latter point calls into question the common belief that local stakeholders have in-depth knowledge of their protected area and a natural commitment to environmental protection. Despite this gap, there is a clear willingness among local communities to adhere to environmental protection laws. This diagnosis led to the updating of the 2023 - 2032 management plan for the Keta Lagoon complex, the first since 1999, aimed at restoring ecosystems, mitigating identified threats, and improving the living conditions of local communities by strengthening their involvement in the sustainable management of the site.